1975
DOI: 10.1007/bf01633825
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphismus der menschlichen Erythrozyten-Esterase D Phänotypenverteilung und Genfrequenzen in Berlin (West)

Abstract: Esterase D phenotypes were determined in a population sample of Berlin (West) by means of high voltage agarosegel electrophoresis. The gene frequencies were calculated with 0.8835 for Es D-1 and 0.1165 for Es D-2. This is consistent with other results obtained in German populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

1976
1976
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
2
1
0
1
Order By: Relevance
“…The low frequencies were observed in African populations and among Europeans living north of the Mediterranean region [2,3,8,13,15,23,24]. The highest EsD2 gene frequencies were found in Lapland, Japan and South Asia [4,8,9,14,24], In our investigation we have found that Ashkenazi and North African Jews present frequencies similar to those of European populations.…”
Section: Discussionsupporting
confidence: 50%
“…The low frequencies were observed in African populations and among Europeans living north of the Mediterranean region [2,3,8,13,15,23,24]. The highest EsD2 gene frequencies were found in Lapland, Japan and South Asia [4,8,9,14,24], In our investigation we have found that Ashkenazi and North African Jews present frequencies similar to those of European populations.…”
Section: Discussionsupporting
confidence: 50%
“…and it did not deviate from results previously obtained for the Copenhagen area (0.7 < p < 0.8) [Sorensen and Fenger, 1976], The distribution of phenotypes in the Danish material did not differ significantly from those reported for neighbouring populations (p>0.05) i.e. Norwegians, North-Germans and Poles [Olaisen et al, 1976[Olaisen et al, , 1981Heide, 1976;Weismanm et al, 1979;Grüner and Simeoni, 1978;Henne and Brinkmann, 1979;Martin and Ott. 1975;Halasa et al, 1980;Koziol and Stepien, 1980], It deviated (p < 0.01) from phenotype distributions found in more remote populations, i.e.…”
Section: Formal Geneticssupporting
confidence: 34%
“…1976;Hopkinson et al, 1973;Koziol and Stepien. 1980;Kühnl et al, 1974;Martin and Ott, 1975;Olaisen et al, 1981;Palscheider and Dirnhofer, 1979;Rittner and Müller. 1975;present study].…”
Section: Application To Paternity Casesunclassified
“…ESD was initially phenotyped by conventional electrophoresis in starch gel using the technique of Kühnl et al |4] and in agarose gel by agarose gel elec trophoresis according to Bär et al |5) and Martin and Otto [8]. Isoelectric focusing was carried out on aga rose gels with pharmalytes (pH range 4.5-S.4) ac cording to Weidinger and Henke (3).…”
Section: Materialsand Methodsmentioning
confidence: 99%